Methodology for determination of rock mass characteristics for hydrotechnical tunnels - Zlatko Zafirovski; Milorad Jovanovski; Igor Peševski (Institute of Water Structures, FCE, BUT, 2015)
The analysis of stress-strain conditions is based on a large number of influential parameters of a rock mass that are very difficult to determine. This paper includes analysis of a large amount of data derived from static and dynamic methods for ground investigation, drill holes and on site measurements. The methods used for investigation are particularly important since we tried to exceed the deterministic approach to analysis, because it does not always allow reliable information for adequate determination of input parameters; thus, the paper advocates the probabilistic approach to analysis. The subject and methodology used in the paper are also mainly related to practical aspects, because final conclusions of investigations are obtained from analysis of a large amount of field and laboratory data, with experiences gained during the design process of hydrotechnical tunnels.
Keywords: rock mass, ground investigation, probabilistic approach, practical aspects, hydrotechnical tunnels.